2014
DOI: 10.1002/eji.201344282
|View full text |Cite
|
Sign up to set email alerts
|

Production of IgG autoantibody requires expression of activation‐induced deaminase in early‐developing B cells in a mouse model of SLE

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the presence of pathogenic IgG anti-nuclear antibodies. Pathogenic IgG autoantibody production requires B-cell activation, leading to the production of activation-induced deaminase (AID) and class switching of IgM genes to IgG. To understand how and when B cells are activated to produce these IgG autoantibodies, we studied cells from 564Igi, a mouse model of SLE. 564Igi mice develop a disease profile closely resembling that found in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…These findings, together with the identification of AID transcripts in B-cell precursors in both mice and humans support the idea that AID expression in immature B cells is relevant to tolerance induction (Han et al, 2007; Kuraoka et al, 2009; Mao et al, 2004; Meyers et al, 2011; Ueda et al, 2007; Umiker et al, 2014). However, it remains to be determined if the AID enzyme is in fact expressed in some B-cell precursors or if central B-cell tolerance defects in AID-deficient patients or mice might be related to their susceptibility to infections in the absence of isotype switched, affinity matured antibodies.…”
Section: Introductionsupporting
confidence: 73%
“…These findings, together with the identification of AID transcripts in B-cell precursors in both mice and humans support the idea that AID expression in immature B cells is relevant to tolerance induction (Han et al, 2007; Kuraoka et al, 2009; Mao et al, 2004; Meyers et al, 2011; Ueda et al, 2007; Umiker et al, 2014). However, it remains to be determined if the AID enzyme is in fact expressed in some B-cell precursors or if central B-cell tolerance defects in AID-deficient patients or mice might be related to their susceptibility to infections in the absence of isotype switched, affinity matured antibodies.…”
Section: Introductionsupporting
confidence: 73%
“…In a different study, pro-B cells from Rag1-deficient mice could be induced in culture to switch at the DNA level from μ>γ2b and from μ>ε, although these cells do not express either μ chains or light chains (67). The physiological role of this H chain switching is unknown, although it might contribute to autoimmunity (68). …”
Section: Csr In B Cell Progenitorsmentioning
confidence: 99%
“…We and others have shown that expression of activation-induced cytidine deaminase (AID) in immature/transitional-1 (T1) B cells is required for the first tolerance checkpoint (Cantaert et al, 2015; Kuraoka et al, 2011; Meyers et al, 2011; Umiker et al, 2014). In the absence of AID, autoreactive immature/T1 B cells are inefficiently purged and exhibit increased resistance to receptor-induced apoptosis (Kuraoka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aicda −/− mice (Umiker et al, 2014). These results are consistent with a significant role for AID in the tolerization of developing B cells, but peak levels of AID expression by immature/T1 B cells reach only about 3% of that present in germinal center (GC) B cells (Kuraoka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%